Influence of the quantity of coloring agent in bleaching gels activated with LED/laser appliances on bleaching efficiency. - Torres, Carlos Rocha Gomes [UNESP]; Batista, Graziela Ribeiro [UNESP]; César, Patrícia Desiderio [UNESP]; Barcellos, Daphne Câmara [UNESP]; Pucci, César Rogério [UNESP]; Borges, Alessandra Buhler [UNESP] (My University, 2009)
The aim of this study was to assess the influence of the quantity of coloring agent on the bleaching efficiency of gels containing 35% H2O2. Sixty human third molars were sectioned mesiodistally, darkened in a coffee solution and sectioned in the occlusal-cervical direction, resulting in mesial (not bleached) and distal halves (bleached). They were distributed into three groups: Whiteness HP, Total Bleach, and Whiteform Perox Red Gel; and subdivided into four sub-groups: no coloring agent, manufacturer's standard, double the standard, and triple the standard. The gels were activated with light-ermitting diode/laser appliances. The images were analyzed with the Adobe Photoshop program (deltaEL*a*b*). The variation was submitted to the ANOVA test (two factors: type of gel and quantity of coloring agent) and Tukey test. Differences were observed for the quantity of coloring agent. The mean (+/-SD) was determined for each quantity of coloring used: no coloring agent -6.85 (+/-2.26)a, manufacturer's standard -794 (+/-2.55)ab, double the standard -8.65 (+/-2.47)b, triple the standard -9.05 (+/-2.72)b. In conclusion, the standard quantity of coloring agent did not provide significantly more intense bleaching than when it was completely absent. The use of double and triple the amount provided greater bleaching than that observed for the gel without coloring agent. No significant differences were observed between the tested gels.